73.9k views
3 votes
If f (x) = 3x + 2 and g(x) = x^2 + 1 which expression is equivalent to ( f o g) (x)

User Stanowczo
by
6.1k points

2 Answers

2 votes

Answer: (f o g)(x)=
3x^(2)+5

Explanation:

To solve this problem you must apply the following proccedure:

(f o g)(x) indicates that you must substitute the function g(x) into the function f(x).

Therefore, you have:

(f o g)(x)=
3(x^(2)+1) +2

Now, you must simplify it, as it is shown below:

Apply the distributive property and add the like terms:

(f o g)(x)=
3x^(2)+3+2

(f o g)(x)=
3x^(2)+5

User Ferrmolina
by
6.4k points
4 votes

Answer:

( f o g) (x) = 3x²+5

Explanation:

We have given two functions :

f (x) = 3x + 2

g(x) = x² + 1

We have to find ( f o g) (x) =?

( f o g) (x) = (f(g(x))

Putting the values of functions in above formula.

( f o g) (x) = 3(x²+1)+2

( f o g) (x) = 3x²+3+2

Adding like terms,we have

( f o g) (x) = 3x²+5

( f o g) (x) = 3x²+5 is the answer.

User Johannes Lund
by
6.0k points